Upper Palaeolithic lithic raw material sourcing in Central and Northern Portugal as an aid to reconstructing huntergatherer societies - Aubry, Thierry (2016)
We present the results of the study of lithic raw materials used in Upper Palaeolithic occupations preserved in caves, rockshelters and open-air sites from two different geological environments in Portugal. For the sites located in the Lusitanian Basin, flint or silcrete sources are easily available in close vicinity. The Côa Valley sites, located in the Iberian Massif, are within a geological environment where restricted fine-grained vein quartz and siliceous metamorphic rocks are available, but no flint or silcrete, even though both are present in the archaeological assemblages. Data from the two clusters of sites are compared with a third newly located site in the Lower Vouga valley, at the limit of the Iberian Massif with the Lusitanian Basin, where quartz vein raw material types are locally available and flint is about 40 kilometres distant. This study reveals prehistoric adaptations to these different geological contexts, with shorter networks for the Lusitanian basin sites contrasting with the long distance ones for the Côa Valley, and the Vouga site at an intermediary position. Finally, we propose that lithic raw material supply networks, defined by a GIS least-cost algorithm, could be used as a proxy not only for territoriality in the case of local and regional lithic raw material sources, but also to infer long-distance social networks between different Palaeolithic human groups, created and maintained to promote the access to asymmetrically distributed resources.